Development and Evaluation of a Sacrificial Film-Forming Barrier Cream for Protection against Cement Dust Exposure (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Construction workers are frequently exposed to cement dust, which can cause skin irritation, dryness, and occupational dermatitis. This study aims to develop and evaluate a sacrificial film-forming barrier cream that provides temporary skin protection against cement dust exposure. Upon application, the formulation forms a thin protective film over the skin, allowing cement particles to adhere to the film rather than directly contacting the skin. After work, the film can be easily removed by washing, carrying the adhered cement particles away and reducing skin exposure. The formulation will be evaluated for film integrity, cement dust adhesion, wash resistance, ease of removal, skin compatibility, spread ability, pH, viscosity, and stability. This approach offers a simple, preventive, and user-friendly strategy for improving occupational skin protection among construction workers.
Keywords: Sacrificial barrier cream; Film-forming formulation; Cement dust protection; Occupational skin protection; Construction workers